Application of renewable energy to provide safe water from deep tubewells in rural Bangladesh - Biswas, Wahidul (The International Energy Initiative, 2010)
Renewable energy can potentially play a role in the supply of safe water in Bangladesh, where nearly 70% of the rural population does not have access to electricity. This paper examines the possible application of renewable energy for pumping water from geologically safe deep tubewells to overcome limitations in existing water technologies in the arsenic-contaminated villages in Bangladesh. Renewable energy, national grid electricity, and alternatives such as diesel engines have been considered as sources of power for both suction and submersible pumps in electrified and non-electrified villages. Three locally available renewable energy sources (human energy, biogas, and solar energy) have been assessed as power sources for reciprocating and submersible pumps. These renewable energy options have not been found cost competitive with the deep tubewells which run off the national grid in electrified villages. However, electricity generated from biogas has the potential to power submersible pumps in non-electrified villages. This paper discusses some financial mechanisms to promote capital-intensive energy options for deep tubewells in arsenic-affected rural areas.